1998
DOI: 10.1046/j.1365-2443.1998.00178.x
|View full text |Cite
|
Sign up to set email alerts
|

A new mammalian period gene predominantly expressed in the suprachiasmatic nucleus

Abstract: Background: In mammals, two possible clock genes (Clock, Per1) have very recently been reported. mPer1 (the first identified mouse period gene), in particular, shows a circadian expression in suprachiasmatic nuclei (SCN), the mammalian circadian centre. However, only mPer1 and Clock as clock components may not be sufficient to understand all the events in circadian oscillation and entrainment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
153
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 222 publications
(167 citation statements)
references
References 25 publications
10
153
0
2
Order By: Relevance
“…5) in which the amplitude of the circadian pacemaker is reduced in Clock mutants, but the perturbing effects of resetting agents such as light or medium changes remain the same. Because Per1 and Per2 oscillate in the SCN in constant darkness and are rapidly induced by light during the subjective night, these two genes have been thought to represent the light-responsive elements of the mammalian circadian pacemaker at the molecular level (8)(9)(10)(11)(27)(28)(29)(30). In this model, we represent PER levels as a state variable in a simple 2D limit cycle oscillator shown diagrammatically in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5) in which the amplitude of the circadian pacemaker is reduced in Clock mutants, but the perturbing effects of resetting agents such as light or medium changes remain the same. Because Per1 and Per2 oscillate in the SCN in constant darkness and are rapidly induced by light during the subjective night, these two genes have been thought to represent the light-responsive elements of the mammalian circadian pacemaker at the molecular level (8)(9)(10)(11)(27)(28)(29)(30). In this model, we represent PER levels as a state variable in a simple 2D limit cycle oscillator shown diagrammatically in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…31 This gene was literally cloned as a secondary mammalian period gene, after Per1. 32,33 However, it has been recently reported that Per1 is not absolutely required for the generation and maintenance of circadian rhythms, 34,35 while Per2 shows a robust cell-autonomous circadian fluctuation in its transcription, being a core component for rhythm generation. Perhaps the lack of correlation between Bmal1 and Per2 found in the visceral fat depot from the patients studied is related to the negative association of Per2 with abdominal fat accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis predicts the existence of a helix-loop-helix motive N-terminal to the PAS-A domain of mPER1, 2, and 3 (5,29,30) and secondary structure predictions suggest this N-terminal region to be mostly α-helical. To explore its potential contribution to homodimer formation, we have determined the dimer affinity of the N-terminally extended mPER3 PAS domain fragment mPER3 , which includes the predicted helix-loophelix motive (Fig.…”
Section: Analysis Of Mper Pas Domain Interactions In Solutionmentioning
confidence: 99%